The peri-ovulatory endocrine millieu regulates the expression of polyamine synthetic pathway in the bovine endometrium - Ramos, R. dos Santos (2012)
Univ São Paulo, Fac Med Vet & Zootecnia, Pirassununga, SP, Brazil